Highly secure adaptive mobile multimedia streaming service - Kimpo, Phillip Jr (2006)
The Highly Secure Adaptive Multimedia Streaming Service (HAMSTER) provides highly secure streaming, sharing, and management of video clips taken using a mobile device. This is accomplished by implementing robust security algorithms in devices with limited computing power and memory, without compromising performance or user satisfaction. The advent of MMS-enabled devices has ushered in a multimedia revolution. We are seeing a shift from old services to the new ones that take advantage of the MMS devices' power and flexibility. While SMS and voice services are still popular, multi-media (specifically video) services are quickly growing in importance and use. However, the management of these videos is laden with problems; mobile devices suffer from limited memory, present video sharing services can use improvement, and security is often an afterthought. HAMSTER addresses these problems by providing users with video albums that they can access anytime, anywhere through a mobile device application and a web application. These albums, along with almost every action within the service, are strongly protected by the HAMSTER cryptosystem.